2018
DOI: 10.1055/s-0038-1646949
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic Dendritic Cells, the Tolerogenic Liver Environment, and Liver Disease

Abstract: The unique liver immune microenvironment favors resistance to inflammation that promotes normal physiological function. At the same time, it endows the liver with tolerogenic properties that may promote pathological processes. Hepatic dendritic cells (HDCs) initiate and orchestrate immune responses depending on signals they receive from the local environment and are thought to contribute to liver tolerance. Thus, HDCs facilitate impaired T cell responses that are observed in persistent hepatitis C virus (HCV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 112 publications
(112 reference statements)
1
36
0
1
Order By: Relevance
“…Additionally, cDC depletion in DTR mice in acetaminophen (APAP) hepatotoxicity could exacerbate liver injury in a manner independent of neutrophils, natural killer (NK) cells or inflammatory mediators 7 . For other liver disorders, the dysfunction of DCs has also been described in previous studies 8 . However, the characterization of cDCs during AIH and the underlying mechanism remain to be elucidated.…”
Section: Introductionsupporting
confidence: 59%
“…Additionally, cDC depletion in DTR mice in acetaminophen (APAP) hepatotoxicity could exacerbate liver injury in a manner independent of neutrophils, natural killer (NK) cells or inflammatory mediators 7 . For other liver disorders, the dysfunction of DCs has also been described in previous studies 8 . However, the characterization of cDCs during AIH and the underlying mechanism remain to be elucidated.…”
Section: Introductionsupporting
confidence: 59%
“…Hepatic dendritic cells show an immature phenotype, with a lower expression of MHC and costimulatory molecules (i.e., CD40, CD86, and CD80), poor endocytotic capacity and low IL-12 production, compared to their peripheral counterparts (81,82). As reported for HDCs, low level expression of costimulatory and MHC class I and II molecules at the steady state makes also KCs, LSECs, and HSCs poorly efficient in , such as TGF-ÎČ and IL-10 can be produced by expanded regulatory T cells (Treg) as well as by stellate cells (HSCs), dendritic cells (DCs) and Kupffer cells (KCs).…”
Section: Tolerogenic Apcmentioning
confidence: 99%
“…Several reports claim that the impairment of MDC function and production of cytokines (IL-12, TNF-α, IFN-α/IFN-ÎČ) in chronic HCV infection. [344][345][346] Laursen et al examined soluble CD163 released from activated liver macrophages in chronic HCV, and histological activity after DAAs. They found that serum CD163 levels decline rapidly after successful DAAs therapy and are associated with histological inflammatory activity and fibrosis.…”
Section: Daas Treatment On Innate Immunitymentioning
confidence: 99%